Brown Adipose Tissue Bioenergetics: A New Methodological Approach. Issue 4 (13th March 2017) - Calderon‐Dominguez, María; Alcalá, Martín; Sebastián, David; Zorzano, Antonio; Viana, Marta; Serra, Dolors; Herrero, Laura
Abstract : The rediscovery of brown adipose tissue (BAT) in humans and its capacity to oxidize fat and dissipate energy as heat has put the spotlight on its potential as a therapeutic target in the treatment of several metabolic conditions including obesity and diabetes. To date the measurement of bioenergetics parameters has required the use of cultured cells or extracted mitochondria with the corresponding loss of information in the tissue context. Herein, we present a method to quantify mitochondrial bioenergetics directly in BAT. Based on XF Seahorse Technology, we assessed the appropriate weight of the explants, the exact concentration of each inhibitor in the reaction, and the specific incubation time to optimize bioenergetics measurements. Our results show that BAT basal oxygen consumption is mostly due to proton leak. In addition, BAT presents higher basal oxygen consumption than white adipose tissue and a positive response to b‐adrenergic stimulation. Considering the whole tissue and not just subcellular populations is a direct approach that provides a realistic view of physiological respiration. In addition, it can be adapted to analyze the effect of potential activators of thermogenesis, or to assess the use of fatty acids or glucose as a source of energy. Abstract : The study of bioenergetics in brown adipose tissue explants is described in this novel methodological approach that utilizes Seahorse technology. This method does not require mitochondrial isolation and detects oxygen consumption in real time. The addition of respiratory inhibitors or thermogenic inducers proves its application to study brown adipose tissue functionality and for antiobesity drug testing.